Isolated renal pelvis injury in case of penetrating injury - Sarma, Debanga; Ghanghoria, Ashish; Barua, Sasanka Kumar; Baruah, Saumar Jyoti; P., Rajeev T.; Bagchi, P. K.; Phukan, Mandeep (International Surgery Journal, 2019)
Isolated renal pelvis injuries are uncommon in a case of penetrating injury. These injuries are associated with other solid or hollow viscous injuries or fractures of transverse process of the adjoining vertebrae. We report a case of a 41year old male involved in a homicidal stab injury. This patient presented with pain abdomen and protrusion of omentum at wound side while CECT whole abdomen revealed extravasation of contrast from left renal pelvis at L3 vertebral level into retroperitoneum with localized collection. He underwent exploratory laparotomy which revealed isolated (Grade III) injury in left renal pelvis with no associated renal parenchymal injury.